Polysaccharide purification from Haemophilus influenzae type b through tangential microfiltration. (13th February 2015) - Albani, Silvia Maria Ferreira; da Silva, Mateus Ribeiro; Fratelli, Fernando; Junior, Celso Preto Cardoso; Iourtov, Dmitri; Cintra, Felipe de Oliveira; Takagi, Mickie; Cabrera-Crespo, Joaquin
Highlights: Simple purification process of polysaccharide produced by Haemophilus influenzae type b suitable for scaling up. Replacement of centrifugation by tangential flow microfiltration technology on H. influenzae type b polysaccharide purification. Purification of polysaccharide produced by H. influenzae type b based on tangential flow microfiltration. Alternative downstream process based on polysaccharide produced by H. influenzae type b for vaccine production. Purification of polysaccharide from H. influenzae type b for vaccines production. Abstract: Haemophilus influenzae type b (Hib) is a human pathogen that causes meningitis in infants worldwide. Capsular polysaccharide linked to a protein has been used as an efficient vaccine, and this approach has reduced the incidence of Hib disease since its inclusion in national immunisation campaigns. The traditional polysaccharide downstream process is based on several ethanol precipitations, treatment with detergents and centrifugation. The aim of this study was to introduce tangential microfiltration (TMF) in the place of centrifugation to simplify handling and to scale up the process. The purity of the polysaccharide was RPNA  = 1747.2 and RPPrt  = 196.1 for nucleic acid and protein, respectively, meeting the quality requirements for this polysaccharide. Moreover, the polysaccharide was recognised by at specific antibody, and the ribose and phosphate contents were within the expected limits. Thus, we established a process for the purification of capsular polysaccharide produced by H. influenzae type b that is effective, robust and feasible to be scaling up.